Short-term simulation training course improves basic obstetric ultrasound operational skills of residents: A multi-center study - Yongfeng Zhao; Ping Zhou; Xiaohong Tang; Wenhui Zhu; Wengang Liu; Jinguang Zhou; Jie Wang; Yingchun Luo; Junhui Zhang; Lan Yang; Yan Xu (PLoS ONE, 2025)
Objectives To evaluate effectiveness of a short-term simulation-based obstetric ultrasound training course. Methods 21 inexperienced trainees and 44 experienced trainees participated in a short-term course about obstetric ultrasound operational skills, which was designed into four task modules. Participants deliberately practiced on simulators for one hour at each module. Their pre-training and post-training operational skill levels were assessed using Obstetric ultrasound competency assessment tool. Likert scale was used to learn about trainees’ confidence before and after training, and their satisfaction with the simulated training course. Results Scores of inexperienced and experienced trainees after training were significantly higher than those before training (inexperienced trainees 20.48 ± 10.64 vs 61.80 ± 15.40, P < 0.001; experienced trainees 39.83 ± 15.00 vs 76.26 ± 12.16, P < 0.001). The passing rate increased from 0% to 90.5% for inexperienced trainees, and from 31.8% to 97.7% for experienced trainees (all P < 0.001). The mastery learning rate increased from 0% to 23.8% for inexperienced trainees, and from 0% to 70.5% for experienced trainees (all P < 0.001). Trainees’ confidence in obstetric ultrasound examination also significantly improved compared to pre-training (2.66 ± 1.12 vs 3.98 ± 0.50, P < 0.001). Most trainees believed that simulation training could help them acquire standardized ultrasound planes (58/60), form organized thinking of scanning (59/60) and improve their competence in following clinical practice (54/60). Conclusions Both inexperienced and experienced trainees can benefit from the short-term simulation training course. Trainees demonstrated strong training satisfaction with the simulation training course.